(untitled) (Sains Humanika, 2017)
The aim of this study is to explore the polytechnic English Language lecturers’ attitudes towards the teaching of Communicative English, which has been introduced in 2010 in the current English syllabus. It also sets out to investigate the challenges the lecturers face in teaching Communicative English syllabus. Participants of this study were 15 English language lecturers teaching at Malaysian Polytechnics and the main mode of data collection was informal interview. Interview data were qualitatively analysed with initial descriptive codes being assigned to lecturers’ responses. Results from the study indicate that the English language lecturers felt that the current Communicative English syllabus could help to prepare students for the workplace needs. However, issues related to students, institutional policy, non-academic tasks and professionalism were reported as challenges in teaching Communicative English courses. This study allows relevant authorities to identify the attitudes and challenges faced by English language lecturers and to facilitate these lecturers who are teaching the new Communicative English syllabus at Malaysian polytechnics.